공과대학생의 일상적 창의성과 보편적 의사소통능력의 상관관계 탐색 - 황순희(Hwang, Soonhee); 윤경미(Yun, Kyung-Mi) (교양교육연구, 2015)
이 연구의 목적은 공과대학생(engineering students)에게 부족하고 미흡하다고 알려진 소프트 스킬(soft skill) 중, 창의성(또는 창의적 능력, creativity)과 의사소통능력(communicative competence)에 주목하여 두 요인 간의 상관관계 및 영향관계를 분석하고, 창의성 및 의사소통능력 함양 유관 교과목 개발 및 전문교양 교육에 설명력을 제공하는 것이다. 창의성과 의사소통능력, 각각의 특성요인 및 개발방법, 교육방안 등에 관해서는 국내외에 상당히 많은 연구가 수행된 바 있으나 창의성과 의사소통능력 간의 관계를 실제 수업 환경과 관련하여 수행한 연구는 찾아보기 힘들다. 이에 본 연구는 일상적 창의성(everyday creativity)과 포괄적 의사소통능력(global interpersonal communication competence)의 필요성을 검토하여 이를 측정 도구로 선정하였으며, 다음 두 가지를 연구의 세부 목표로 설정하였다. 첫째, 공과대학생의 일상적 창의성과 포괄적 의사소통능력을 측정하여 학년별, 성별 차이를 분석하고, 둘째, 두 변인을 구성하는 하위 요인들 간의 상관관계, 영향관계를 분석하는 것이다. 연구 결과, 첫째, 공과대학생의 일상적 창의성은 성별, 학년에 따라 유의한 차이를 보이지 않았다. 둘째, 포괄적 의사소통능력은 성별, 학년에 따른 유의한 차이를 보이지 않았다. 셋째, 일상적 창의성과 포괄적 의사소통능력 간에는 높은 정적 상관이, 아울러 세부 하위 항목 간에도 높은 정적 상관이 확인되었다. 이 연구는 창의성과 의사소통능력 간의 상관관계를 직접 논의한 연구가 없는 상황에서 두 요인 간의 밀접한 상관성을 밝혔다는 점에서 의의가 있으며 이를 기초로 향후 유관 교과목 개발과 개선방안 모색에 시사점을 제공할 수 있으리라 기대한다. This study aims to analyze the correlation between ‘creativity’ and ‘communicative competence’ as well as their influencing relationships, and finally to provide an explanation for the development of related fields and education. It has been reported that engineering students lack the two soft skills, creativity and communicative competence. However, according to the examination of both domestic and overseas researches concerning the relationships between creativity and communicative competence, few studies have focused on them in terms of the engineering curriculum. This study was conducted with 286 engineering students at P University, and especially their ‘everyday creativity’ and ‘global interpersonal communicative competence’ have been evaluated. Our findings showed that firstly, there were no significant gender and grade differences in everyday creativity of engineering students. Second, there were no significant gender and grade differences in global interpersonal communicative competence. Third, we found a high correlation between the two factors, creativity and communicative competence. Also there was a high correlation among variables of subcategories. Based on these findings, it is requested to verify the validities of lack of significant differences in everyday creativity and global interpersonal communicative competence and refine the improvement plans for the related general education in university. KCI Citation Count: 18